Analysis of the Water Footprint of Central and Eastern Europe Countries - Panasiuk, Damian; Skrypchuk, Petro; Kucharska, Barbara; Suduk, Olena (Studia Ecologiae et Bioethicae, 2022)
The article presents an analysis of the water footprint of five Central and Eastern European countries, i.e. Poland, Slovakia, Lithuania, Ukraine and Belarus. The first three are members of the European Union, the other two are not. These countries also differ in terms of climate. The green, blue and grey water footprints of crop production, grazing, animal water supply, industrial production and domestic water supply are analysed. The per capita water footprint is also calculated. It is the highest for the countries of the former Soviet Union, that is Ukraine, Belarus and Lithuania, and half as low for Poland and Slovakia. In the case of virtual water, Poland dominates in the area of import, and Ukraine in export. The index of the net import of virtual water is unfavourable for Ukraine and Lithuania and is much more positive for Poland and Belarus. When calculated per capita, the net import of green virtual water is the highest for Belarus (340 m3/person/year) and Poland (148 m3/person/year). A positive value of this index was also recorded for Slovakia and negative for Lithuania and Ukraine (-282 m3/person/year). Taking into account the exposure of the southern Ukraine steppe to water stress, this is not a favourable situation for greater export of virtual water than its import.